Utilization of Technology-Aided Strategies in Teaching Social Science: Basis for Outcomes-based Instruction - Hernando L. Bernal Jr; Hazel D. Cao; Alvin A. De Sierra; Cassandra A. Diamaton; Cristine Denise Dolor; Angelo I. Hidalgo; Maybel V. Pati (Randwick International of Education and Linguistics Science Journal, 2023)
One of the major problems in teaching social sciences is finding the appropriate strategies to deliver the lessons to students. The researchers are determined to develop proper guidelines in using educational strategies to improve the learning process, one of which is the Utilization of Technology-Aided Strategies, that a social science teacher could implement inside the four corners of the classroom, especially in the 21st century, where one of the major problems of teachers are engaging students’ participation. Descriptive quantitative research method was used in conducting this study. Through the process of purposive sampling technique, a total number of 50 teachers in a national high school was selected to participate in the study. The major instruments used were survey questionnaires. The data gathered were analyzed. The findings demonstrated the importance of understanding the Utilization of Technology-Aided Strategies, when it comes to teaching Social Science. In order to make sure that the right tools and materials were available for them to work with, teachers should be aware of the profiles and learning styles of the learners. The teaching and learning process should be improved by teachers and school officials, boosting its effectiveness and efficiency.